Gender report: Training of trainers of socio-technical innovation bundles in agriculture and livestock. Building equitable climate-resilient African bean and insect sectors - Siri, Bella Ngoh; Djembissi, Irène Kuetche; Nana, Paulin; Hortense, Mafouasson; Nchanji, Eileen (2025)
As part of the BRAINS Project in Cameroon, a series of participatory workshops was held in September 2025 to co design and strengthen the implementation of socio-technical innovation bundles (STIBs) to improve agricultural productivity, sustainability, and inclusiveness. The workshops brought together 100 diverse stakeholders from the bean, insect, and fruit value chains, as well as actors involved in processing, marketing, and value addition across these sectors. The workshop aimed to train core groups of competent trainers capable of transferring the knowledge and practices they acquired to producers, cooperatives, and rural organisations. The main goal was to strengthen the capacities of these trainers on STIBs to enhance bean and fruit tree cultivation, promote integrated pest management (IPM), modern beekeeping, and sustainable black soldier fly (BSF) breeding. The training sessions took place in Bamendjou, Mfoumbot, Mbouda, and at IRAD Foumbot, on the 15, 16, and 17 September 2025 in the West Region of Cameroon, combining theoretical presentations and hands-on field exercises. The workshops were divided into three main phases: 1. Knowledge sharing on innovative agricultural techniques, including pest fly control using pheromone traps, pollination management, and the use of biofertilizers, biopesticides, and drones for crop management. 2. Demonstrations and practical fieldwork to apply these techniques in real production settings. 3. Discussions on gender and social inclusion within agricultural innovation systems. A significant component of the workshops focused on gender integration, led by the BRAINS Project gender focal people, Dr Irene Flore Kuetche and Dr Siri Bella. The gender sessions aimed to raise awareness on gender transformative socio-technical innovation bundles (STIBs) and emphasised four key objectives: • Ensuring that 60% of direct beneficiaries are women, girls, and young people, contributing to the project’s goal of reaching 10 million direct and 50 million indirect beneficiaries. • Enhancing climate resilience, leadership, and agency among women and youth in bean and insect production systems. • Scaling climate-smart agricultural technologies in a gender-responsive manner to strengthen resilience across production systems. • Catalysing gender-responsive business development, supporting enterprises that invest in carbon-neutral, climate-resilient agriculture benefiting women and youth. The sessions also clarified the distinctions among gender equality, equity, justice, and inclusion through practical examples. Discussions highlighted women’s and youth’s participation, access to resources and information, empowerment, and leadership in transforming agricultural systems. Examples such as BSF production and beeswax value addition were used to illustrate how gender-transformative STIBs can empower women and youth in agri-enterprise development. A vibrant discussion identified key challenges faced by women and young people, including restrictive social norms, limited economic and social power, family constraints, and low confidence or ambition. In response, several women’s groups were identified for further engagement, and the project committed to future capacity building sessions to strengthen their participation and leadership in agricultural innovation.